RETORIKA USTADZ ABDUL SOMAD - Rozita, Rozita; Charlina, Charlina; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discusses the technique of rhetoric of Ustadz Abdul Somad. The data in this study was obtained from Ustadz Abdul Somad's lecture "Beautiful Life Under Shade of Islamic Shariah, Five Preparations for the Holy Month of Ramadan, Tablig Akbar HUT Kab. The 19th Right Way, and the Favors of Independence ". This research is qualitative research. Data techniques are downloading, viewing and listening. The results of this study indicate that the techniques used Ustadz Abdul Somad in the lecture of ethos techniques, pathos, logos, and rekreatif. From the results of the dominant technique research is the ethos technique used Uastad Abdul Somad from other techniques. Meaning that Ustadz Abdul Somad does have extensive knowledge. That is also the reason why Ustadz Abdul Somad is loved by many circles. Because each submitted is always accompanied by data that makes the listener sure about what it says.Keywords: Rhetoric, Ustadz Abdul Somad